Reformacija i apokalipsis sekuljarnosti - Cherenkov, Mykhailo (Bogoslovskie razmyšlenija, 2017)
The article is devoted to the conceptualization of Reformation and secularism in their correlation. The emphasis is made not as much on the historical or theological reading of the post-reform history of the secular world, but more so on the metahistorical and apocalyptic. A distinction is made between the secular apocalypse and the apocalypse of secularism. Secular apocalypse can be understood as the revelation of a person about himself, a revelation of suicide and dystopia. The apocalypse of secularism sets a very wide framework, returns secularity to the history of God’s revelation, in which there is a place for both death and resurrection. The author comes to the conclusion that secularism was a necessary, although a transitional stage in the history of relations between church and society; and in this sense, it can be referred to as the "unintended Reformation," which for Christians appeared to be not as much as an elaborate plan but as an amazing revelation.